1991 LEGISLATIVE ANALYSIS MICHIGAN (Tufts Archival Research Center, 2007)
Analysis of the legislative situation in Michigan. Discusses the races in which there are candidates supportive of the tobacco industry and the actions the industry should take after the outcome is determined. Provides summaries of two races in which important candidates are running and the activities of the tobacco industry in order to help their preferred candidate win.